2000
DOI: 10.4049/jimmunol.164.6.3026
|View full text |Cite
|
Sign up to set email alerts
|

Dual Phase Priming by IL-3 for Leukotriene C4 Generation in Human Basophils: Difference in Characteristics Between Acute and Late Priming Effects

Abstract: Previous studies have suggested that enhancement of mediator release from human basophils by IL-3 occurs in at least two phases, and the current studies further characterize the signaling changes that accompany these two phases of the basophil in response to IL-3. The test stimulus for these studies was anaphylatoxin split product of C component (C5a), which does not induce leukotriene C4 release without prior IL-3 treatment. Functionally, IL-3 priming occurs after 5 min, disappears by 2 h, and returns by 18 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
(76 reference statements)
1
23
0
Order By: Relevance
“…We chose 4 growth factors, IL-3, IL-5, GM-CSF, and NGF, which all acutely prime basophils with similar efficacy, 10,25,26 as well as cytokines thought to enhance cytotoxic functions of lymphocytes (IL-2, interferon-␣, and interferon-␥). The efficacy of IL-3 to induce GzmB was rather unique since only weak effects were observed in 31,32 and the induction of GzmB expression shows an identical pattern and order of efficacy of the cytokines (IL-3 Ͼ Ͼ Ͼ NGF Ͼ IL-5 Ͼ GM-CSF), while IL-3 and NGF were similarly effective in enhancing C5a-induced degranulation. A similar pattern of responses was found using different doses of IL-3.…”
Section: Induction Of Granzyme B Expression By Cytokines and Supernatmentioning
confidence: 97%
See 2 more Smart Citations
“…We chose 4 growth factors, IL-3, IL-5, GM-CSF, and NGF, which all acutely prime basophils with similar efficacy, 10,25,26 as well as cytokines thought to enhance cytotoxic functions of lymphocytes (IL-2, interferon-␣, and interferon-␥). The efficacy of IL-3 to induce GzmB was rather unique since only weak effects were observed in 31,32 and the induction of GzmB expression shows an identical pattern and order of efficacy of the cytokines (IL-3 Ͼ Ͼ Ͼ NGF Ͼ IL-5 Ͼ GM-CSF), while IL-3 and NGF were similarly effective in enhancing C5a-induced degranulation. A similar pattern of responses was found using different doses of IL-3.…”
Section: Induction Of Granzyme B Expression By Cytokines and Supernatmentioning
confidence: 97%
“…The most efficient cytokine inducing GzmB together with other phenotypic and functional alterations is IL-3. [30][31][32] An identical concentration range of IL-3 induces GzmB expression and the persistent facilitation of LTC 4 formation. When the effect of different cytokines was compared, we observed an identical order of efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the results of their study may have been influenced by technical problems, as basophile histamine release after C5a stimulation was very low in the healthy controls, who released only around 4% of the histamine content after C5a stimulation. In contrast, an earlier study by Miura and MacGlashan [17], for example, and a recent study by Marsland et al [18] have shown that basophils of normal donors release about 40% of their histamine content after C5a stimulation. Calcineurin inhibitors were able to inhibit the in vitro release of histamine when basophils were stimulated with urticaria sera but not when stimulated with C5a [18].…”
Section: Discussionmentioning
confidence: 72%
“…We found that MG-132 and other proteasome inhibitors induced significant apoptosis of basophils cultured for only 18–24 h. This result led to the conclusion that results using agents that altered apoptosis would be difficult to interpret. Although 18 h of treatment of basophils with cycloheximide does not appear to cause changes in viability [29], incubation with protein synthesis or transcriptional inhibition reverse the effects of IL-3 [29], and IL-3 promotes survival in basophils [28,30]. In light of this, the actinomycin D and cycloheximide data should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%